ASSESSMENT OF COMPENSATION POLICIES IN A PUBLIC HOSPITAL FROM ROMANIA. CASE STUDY: SLATINA COUNTY EMERGENCY HOSPITAL - Cătălin Ștefan ROTEA (Management & Marketing)
Individual and collective employee and employee reward and productivity are the central drivers of activity in any type of organization. In the medical sector, due to the challenges posed by the phenomenon of emigration of employees in the area, identifying policies and ways to retain and motivate talented human resources is essential in order to provide a quality medical act. In order for an organization to be able to effectively manage rewards and to have a positive influence on the performance of its employees, organizations' management must understand the different aspects of the rewarding process as a driving force motivating employees and directing their behavior towards organizational goals. In this paper we proposed a tool for evaluating reward policies within a hospital in the Romanian public health care system. This tool was used in the Slatina County Emergency Hospital, which allowed us to analyze reward policies and their impact on hospital activity.